PERKEMBANGAN DAYAH RAUDHATUN NAJAH DAN PERKEMBANGAN PENDIDIKAN ISLAM DI KOTA LANGSA TAHUN 2006 - 2017 - Nurhani (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2021)
Dayah Raudhatun Najah in Langsa City, was founded by a competent teacher in 2006 by Tengku H. Ridwan Gapi, S.Ag with the legal status of Dayah (Legal Entity) No.C-52.HT.03.01-Th 1993 and currently has a land area of ​​15,200 m2, which is able to make Dayah Raudhatun Najah in Langsa City, ready to compete with more qualified and well-known dayahs out there, besides Dayah Raudhatun Najah in Langsa City, also brings a good influence to the local community and also the younger generation. Dayah Raudhatun Najah also has many advantages including organizing the learning of the Turats or yellow books at all levels of education and an integrated system, which combines general education and religious education. Suggestions in writing this to other writers to be able to continue research in more depth so that they can add knowledge in the future, especially so that it can be useful for all of us.